2017
DOI: 10.1103/physrevb.95.075434
|View full text |Cite
|
Sign up to set email alerts
|

Planar heterostructures of single-layer transition metal dichalcogenides: Composite structures, Schottky junctions, tunneling barriers, and half metals

Abstract: Planar composite structures formed from the stripes of transition metal dichalcogenides joined commensurately along their zigzag or armchair edges can attain different states in a two-dimensional (2D), single-layer, such as a half metal, 2D or one-dimensional (1D) nonmagnetic metal and semiconductor. Widening of stripes induces metal-insulator transition through the confinements of electronic states to adjacent stripes, that results in the metalsemiconductor junction with a well-defined band lineup. Linear ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
(50 reference statements)
5
27
0
Order By: Relevance
“…In this respect, the stability of bilayers and multilayer stacks is also enhanced. Recent theoretical stability analysis 29,35 and extensive structure optimization calculations carried out here as well as recent experimental studies 7,27,28,33,36−38 indicate that the vertical and lateral heterostructures treated in the present study are stable and can be fabricated. It should also be pointed out that lateral homojunctions combining hexagonal (semiconducting) and monoclinic (metallic) phases of MoTe 2 have already been fabricated via laser-induced phase patterning.…”
Section: ■ Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this respect, the stability of bilayers and multilayer stacks is also enhanced. Recent theoretical stability analysis 29,35 and extensive structure optimization calculations carried out here as well as recent experimental studies 7,27,28,33,36−38 indicate that the vertical and lateral heterostructures treated in the present study are stable and can be fabricated. It should also be pointed out that lateral homojunctions combining hexagonal (semiconducting) and monoclinic (metallic) phases of MoTe 2 have already been fabricated via laser-induced phase patterning.…”
Section: ■ Introductionsupporting
confidence: 61%
“…The electronic structure of 2D SL MoTe 2 and NiTe 2 as well as the energetics and thermal stability of zigzag or armchair edged lateral heterostructures were discussed in our previous study. 29 In the present study we consider features which were not treated earlier. Moreover, we contrast these features with those of the vertical heterostructures.…”
Section: ■ Resultsmentioning
confidence: 99%
“…[134][135][136] Composite structures made of lateral and vertical junctions of 2D SL structures like Graphene/BN or MoS 2 / WS 2 that have been previously treated both theoretically and experimentally, heralded great potential for new generation artificial structures with promising applications. 20,[137][138][139][140][141] Motivated with the synthesis of very thin h-GaN and h-AlN, Onen et al 35 recently studied the composite structures of their single-layers. They showed that stable, in-plane composite materials, (GaN) p /(AlN) q can be constructed of periodically repeating stripes of GaN and AlN continuously (or commensurately) joined along their zigzag (Z) edges.…”
Section: Composite Structures Of Gan/alnmentioning
confidence: 99%
“…The Schottky-Barrier height plays an important role in the transport properties of of SBFETs. Recent theoretical study demonstrates the linear bending of the band edges of the semiconductor at the boundary between the metal and semiconductor will affect the Schottky-Barrier height effectively [35]. Following their method, we calculate the Schottky-Barrier height of our devices from the local density states (LDOS), the transmission spectrum and the averaged potential along Z direction in Fig.…”
Section: Model and Simulation Approachmentioning
confidence: 99%